2020
DOI: 10.3389/fpsyg.2020.02027
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Relational Well-Being at the Start of an ART Treatment: A Focus on Partners’ Gender Differences

Abstract: Infertility and ART treatments represent stressful experiences for the couples, impacting on the overall psychological well-being of partners as well as on their couple adjustment. Several variables were analyzed as risk factors for infertility-related distress. The impact of these experiences has been well-documented in both women and men, reporting important gender differences. The aim of this study was to assess gender differences in individual and relational well-being in infertile couples. Gender differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…Moreover, men who access ARTs (due to their heterosexual condition and with a partner or through surrogate motherhood in certain countries) present an emotional involvement and affectation before ARTs comparable to that experienced by women. Social support is fundamental for men's and women's mental health in assisted reproduction processes (Molgora et al, 2020). Specifically, in this study, women were more aware of this need for support and social debate about ARTs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, men who access ARTs (due to their heterosexual condition and with a partner or through surrogate motherhood in certain countries) present an emotional involvement and affectation before ARTs comparable to that experienced by women. Social support is fundamental for men's and women's mental health in assisted reproduction processes (Molgora et al, 2020). Specifically, in this study, women were more aware of this need for support and social debate about ARTs.…”
Section: Discussionmentioning
confidence: 78%
“…In situations of low social support, women present more depression and men present more anxiety. In conclusion, gender differences and ARTs can influence both partners and the adjustment of a couple's relationship (Molgora et al, 2020).…”
Section: Conflicting Positions In Assisted Reproductive Treatmentsmentioning
confidence: 92%
“…The psychological and psychosocial interventions, based on the multidisciplinary dialogue with the doctor who performed the diagnosis, in this phase are aimed at preventing the development of psychological distress ( Van den Broeck et al, 2010 ; Frederiksen et al, 2015 ; Molgora et al, 2020 ) and analyzing with the couple the scenario in which the choice to arrive at a center for ART treatments occurs. Inside (or outside) the couple, by whom is the decision made?…”
Section: The Female’s Journey In Art Treatments: Suspended Identitiesmentioning
confidence: 99%
“…Partners’ health behaviors and overall life satisfaction during the diagnosis and treatment of infertility can be important factors in making it easier for potential parents to undergo medical procedures and rigors. Several studies found that there are gender differences in experiencing infertility [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%